2011
DOI: 10.1167/iovs.10-7127
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vision Impairment on Vision-Specific Quality of Life in Germany

Abstract: Using a psychometrically valid German IVI, even mild vision impairment was independently associated with poor VRQoL. These findings reinforce the importance of early preventative and rehabilitative efforts to prevent longitudinal deterioration in vision loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
4
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 38 publications
8
76
4
6
Order By: Relevance
“…The modified VF-9 scale that fits the Rasch model provides more accurate scoring of visual functioning compared with other studies that have used mean or summary visual functioning scores 22 23. Rasch analysis is increasingly considered the gold standard of modern scale validation, and can be used to look at the impact of cataract surgery on visual functioning 1. On the other hand, our study population included only Singaporean Malay individuals and our study findings cannot be generalised to other populations.…”
Section: Discussionmentioning
confidence: 97%
“…The modified VF-9 scale that fits the Rasch model provides more accurate scoring of visual functioning compared with other studies that have used mean or summary visual functioning scores 22 23. Rasch analysis is increasingly considered the gold standard of modern scale validation, and can be used to look at the impact of cataract surgery on visual functioning 1. On the other hand, our study population included only Singaporean Malay individuals and our study findings cannot be generalised to other populations.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the 32-item IVI, the 28-item version also was demonstrated to lack unidimensionality, albeit in a German VI population. 50 Taken together, these studies bear out that optimal functioning in another population should not be assumed. Rather, questionnaires should be revalidated in the population in which they are intended to be used.…”
Section: Discussionmentioning
confidence: 98%
“…We and others have previously reported that even mild visual impairment (0.3<LogMAR<0.5) has a significant and independent impact on vision-specific functioning 41–43. Similarly, emotional well-being is affected in patients with even mild vision impairment 42. Depression is considered to result in further functional decline in this group by reducing motivation, initiative and resiliency 44–46.…”
Section: Discussionmentioning
confidence: 99%